UNRELIABLE NARRATOR: REPARATIVE APPROACHES TO HARMFUL BIASES IN AI STORYTELLING FOR THE HE CLASSROOM AND FUTURE CREATIVE INDUSTRIES - Jackson, David; Courneya, Marsha (Brazilian Creative Industries Journal, 2023)
.